Mud prone entrenched deep-water slope channel complexes from the Eocene of eastern Turkey - Cronin, Bryan T.; Celik, Hasan; Hurst, Andrew; Turkmen, Ibrahim (Geological Soc Publishing House, 2005)
A series of deep-water channel deposits are exposed near Baskil, 50 km west of Elazig in eastern Turkey. The use of correlation panels, sedimentary logs, biostratigraphy and mapping revealed that all of the channel elements are found within much larger features. One series of channels from the southern margin of the basin lie, within an entrenched deep-water slope channel complex, over 3 km wide, called the Nohut Channel Complex. This channel complex has three main fill packages. The lower package is a highly disturbed, slumped interval that directly overlies the erosional base of the main channel complex. The slumped interval is interpreted as a series of mass transport complexes, derived from shallow marine or upper slope facies. The second package comprises a mixed carbonate-siliciclastic series, principally of interbedded calcarenites, marls and mudstones. Locally, outer shelf/upper slope offset-stacked channels with calcarenite fills occur. The upper package comprises isolated conglomerate and sandstone filled deep-water channels that are incised into laterally extensive depositional lobes. The coarse-grained fills are dominated by tabular beds. The lobes are comprised of fine-medium grained sandstones. Some of these channels have low aspect ratios (25:1), and are asymmetric in cross-section, suggesting sinuosity. The upper part of this fill package is either incised into by pro-fan delta conglomerate filled channels, or down-lapped onto by shelfal calcarenites. A separate series of channels come from the northern margin of the basin, but are interpreted to have developed on an open, deep-water slope or ramp, rather than as an entrenched channel complex. These channels occur in two main sets, collectively referred to as the Aydinlar Channel Complexes. The lower set is characterized by syn-sedimentary foundering of the sand-filled channels within slumped enveloping finer-grained slope sediments. The upper set of channels, dominated by one large sand and gravel-filled fairway, is characterized by large bedforms at the base, passing upwards into stacked conglomerates, mud chip breccias and sandstones. The conglomerate facies is locally injected upwards into the fill or laterally into finer-grained marginal facies. The channel is capped by finer-grained facies, including graded sandstones and siltstones with complete Bouma sequences.
Keywords: Sea; Fan